The significance of english for specific purposes approach for first year law degree students at the University of Limpopo - Moremi, Katlego Tennic (My University, 2021)
The purpose of this study was to investigate the significance of English for Specific Purposes (ESP) approach for the first year Law Degree students at the University of Limpopo. Qualitative, ethnographic research was conducted to determine the views and perceptions of the participants. Data was collected through interviews and questionnaires with a selected sample of respondents, and the data was analysed using thematic analysis. Themes were generated to present the data based on the objectives of the study, which were aligned to the literature review. The study has highlighted how the ESP approach could be used in the existing English module drawing from the participants’ conceptions. The findings revealed that even though the English module is considered important in the law degree by students and lecturers, the content of the module should be designed in a manner that fits the Law field. The study recommends that relevant content be designed to develop essential skills such as problem-solving and critical thinking and the module content should be designed with the specific content that fits the law degree.
Thesis (M.A. (English Studies)) -- University of Limpopo, 2021
Keywords: English for specific purposes; English module; Law degree; Needs analysis; Course design; English language; English language -- Study and teaching; Law students